Immunohistochemical study of p53 expression in premalignant and malignant cervical neoplasms - Tan GC,; Sharifah NA,; Salwati S,; Hatta AZ,; Shiran MS,; Ng HO, (Penerbit UKM, 2007)
One of the most important cervical cancer risk factors is human papillomavirus (HPV) infection. The p53 gene is one of the most important targets of the HPV E6 gene. E6 protein has the ability to stimulate p53 degradation, inhibits several functions of wild-type p53 and it competes with its function including suppression of malignant growth. The aim of this study is to determine the differences in p53 expressions in pre-malignant and malignant cervical neoplasms. This is a retrospective study on 100 cases of cervical neoplasms. There were 21 cases of CIN 1, 8 cases of CIN 2, 25 cases of CIN 3, 36 cases of squamous cell carcinoma, 7 cases of adenocarcinoma and 3 cases of adenosquamous carcinoma. All cases were evaluated by immunohistochemistry using p53 monoclonal antibody. Thirty six of the 54 pre-malignant cases (66.7%) were positive for p53 protein, in contrast to the malignant cases in which, 40 of the 46 cases (87.0%) were positive. The majority of CIN showed absent to focal staining (29/54, 53.7%). In contrast, 84.8% (39/46) of the invasive carcinoma showed regional to diffuse staining. The expression of p53 is greater in the malignant cervical neoplasms than the pre-malignant cervical lesions, suggesting that p53 overexpression is not an early phenomenon in the pathogenesis of cervical cancer. It is also shown to be slightly higher in percentage in CIN 2 and 3 when compared with CIN 1. However, a number of cases were p53 negative, suggesting that other factors may be involved and further HPV studies are indicated